Znaczenia technologii informacyjnej w ocenianiu usługodawców logistycznych - Grabara, Janusz (Meanings of Informations Technology in Third-Party Logistics Evaluations, 2005)
The paper presents problems connected with IT importance in logistics service providers evaluation The Author points on basis functions realised by the logistics service providers and he also gives proposal of the logistics evaluation estimates.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 303-308